TEXT MINING AND TEXT ANALYTICS OF RESEARCH ARTICLES - Akshaya Udgave , Prasanna Kulkarni (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
There has recently been a tremendous increase in published articles and research papers. Such documents are stored in electronic format, but the data is semi-structured or unstructured. The analysis of the patterns and trends is an enormous task. Text mining is therefore extensively researched today. Text Mining extracts appropriate knowledge from the text documents. Different text mining techniques convert unstructured data to structured data. Text classification, one of the basic principles of text mining, requires a number of techniques for processing text, the most important being Natural Language Processing (NLP). Text Mining simplifies data and is useful to researchers, scientists, and academics. Various analytics tools are used for deriving relevant and in-depth information and inferences from the mined text. This paper studies various text mining techniques, and discusses recent advances in the field of design science.